Critical Discourse Analysis of the Indonesian Exemplary Father Movement (Gati) Campaign on Instagram @Gatikemendukbangga - P., Retno Dewanti; Lusianawati, Hayu (Eastasouth Institute, 2026)
This study analyzes the digital campaign of the Indonesian Exemplary Father Movement (Gerakan Ayah Teladan Indonesia/GATI) on Instagram as a discursive practice that constructs meanings of fatherhood within contemporary Indonesian society. Using Norman Fairclough’s Critical Discourse Analysis (CDA) framework, this research examines three interrelated dimensions: textual representation, discursive practices, and social practices. The data consist of fifteen purposively selected Instagram posts published between September and December 2025 on the official @gatikemendukbangga account, including captions, visuals, hashtags, and public interactions. The findings reveal that the GATI campaign consistently frames fatherlessness as a psychosocial and national crisis through emotional metaphors and affective visuals, while simultaneously constructing the figure of the “exemplary father” as emotionally present, morally responsible, and central to family resilience and human development. At the level of discursive practice, the campaign demonstrates strong institutional control through standardized narratives, visual styles, and participatory calls to action that encourage normative internalization rather than critical debate. At the level of social practice, the campaign operates as a form of symbolic governance, where the state rearticulates masculinity by promoting caring fatherhood while maintaining paternal centrality within a patriarchal framework. This study contributes to critical communication and fatherhood studies by positioning state-led digital campaigns as sites of ideological negotiation, highlighting how public policy discourse shapes family norms, gender relations, and moral subjectivity in the digital public sphere.